2022
DOI: 10.1039/d1en00937k
|View full text |Cite
|
Sign up to set email alerts
|

The photocatalytic NO-removal activity of g-C3N4 significantly enhanced by the synergistic effect of Pd0 nanoparticles and N vacancies

Abstract: Graphite carbon nitride (g-C3N4) has been proven to have photocatalytic activity for NO-removal under visible-light irradiation. However, the competitive adsorption between NO and O2 during the process may decrease the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…10 In addition, the O 2 adsorption capability on the TBCN@3% rGO was also estimated by O 2 -TPD analysis, which is an essential parameter in both the H 2 O 2 production and alcohol oxidation reaction (Figure 6c). 60 The O 2 -TPD profile of TBCN@3%rGO exhibited three types of desorption signals as shown in Figure 6c. A weak desorption signal of O 2 appeared at 200−280 °C, which suggests that a very small amount of O 2 was desorbed at this temperature range.…”
Section: Light Absorption Properties and Flat Band Positions (Uv And ...mentioning
confidence: 52%
See 2 more Smart Citations
“…10 In addition, the O 2 adsorption capability on the TBCN@3% rGO was also estimated by O 2 -TPD analysis, which is an essential parameter in both the H 2 O 2 production and alcohol oxidation reaction (Figure 6c). 60 The O 2 -TPD profile of TBCN@3%rGO exhibited three types of desorption signals as shown in Figure 6c. A weak desorption signal of O 2 appeared at 200−280 °C, which suggests that a very small amount of O 2 was desorbed at this temperature range.…”
Section: Light Absorption Properties and Flat Band Positions (Uv And ...mentioning
confidence: 52%
“…It signifies that the TBCN@3%rGO contains the required acidic sites, which are essential in the adsorption and activation of alcohols on the catalyst surface . In addition, the O 2 adsorption capability on the TBCN@3%rGO was also estimated by O 2 -TPD analysis, which is an essential parameter in both the H 2 O 2 production and alcohol oxidation reaction (Figure c) . The O 2 -TPD profile of TBCN@3%rGO exhibited three types of desorption signals as shown in Figure c.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Pristine Environmental Science: Nano Paper CN revealed typical peaks at 12.9 and 27.9°, corresponding to the (100) and (002) planes. 23 The former was derived from the in-plane packing of s-triazine and the latter originated from the interlayer stacking of CN heterocycles. 16 Under the influence of WCN, the peak at 27.9°red-shifted to 27.96°, suggesting intense interactions between CN and WCN (ESI, † Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen defects in g-C 3 N 4 usually can adjust the energy band structure, broaden the light absorption range, and act as the active sites for reactant molecules in the reaction system. [28][29][30][31] A variety of defect-induced visible-light photocatalytic performance enhancements in g-C 3 N 4 have been carried out. For example, Zhang et al 32 found that the introduction of nitrogen defects (cyano groups and surface N vacancies) into g-C 3 N 4 could facilitate the separation of electron/hole pairs and redshift the g-C 3 N x absorption edge.…”
Section: Introductionmentioning
confidence: 99%